'Eternal convivencia': From Madrid's Painters of Africa to the School of Tetouan. Issue 1 (2nd January 2023) - Hopkins, Claudia
Abstract : The annual Pintores de África exhibitions, organised by Franco's colonial administration in mid-twentieth-century Madrid, offered audiences a colourful feast of artistic representations of Spain's colonial territories in Africa, and of Spain's architectural legacy of al-Andalus. Foregrounding the ideological issues underpinning these exhibitions, this article evaluates the selection of artworks, the programme of events, exhibition catalogues, and reviews. Many writers discussed the artworks with reference to al-Andalus, echoing colonial propaganda. After Moroccan independence (1956), the exhibitions partly lost their purpose, but the memory of al-Andalus was repurposed by Moroccan cultural brokers for the fashioning of their post-colonial artistic identity. The last part of this article reveals the relations between the Painters of Africa exhibitions and the birth of the School of Tetouan. The article not only sheds light on the art, curation, and art writing that took place in the interstices between Spain and Morocco at the end of colonialism, but also illuminates the paradoxical processes underpinning the formation of artistic identity in post-independence northern Morocco. The case study is relevant to global perspectives in History of Art and refigures understandings of East–West relations with which we have become so familiar since Said's Orientalism of 1978.